Senegal : 2021 Article IV Consultation, Fourth Review Under the Policy Coordination Instrument, First Reviews Under the Stand-By Arrangement and the Arrangement Under the Standby Credit Facility, and Request for Modification of Performance Criteria and Quantitative Targets. (IMF Staff Country Reports; Country Report ;, 2022)
The COVID-19 pandemic interrupted a decade of high growth and development progress in Senegal. While a recession was avoided in 2020, the pandemic caused severe hardship and most households experienced income and job losses. A dynamic recovery is underway since mid-2020, supported by expansionary fiscal policy. However, higher fiscal deficits and lower growth have resulted in a rapid increase of the debt-to-GDP ratio and fiscal space is narrowing. COVID-19 case numbers remain comparatively low and about 14 percent of the adult population is vaccinated. Recent pandemic waves had little impact on economic activity in the absence of new lockdowns or movement restrictions.